2016
DOI: 10.2340/00015555-2395
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Cream Containing Ceramides and Magnesium in the Treatment of Mild to Moderate Atopic Dermatitis: A Randomized, Double-blind, Emollient- and Hydrocortisone-controlled Trial

Abstract: The aim of this randomized controlled trial was to assess the efficacy of a cream containing ceramides and magnesium (Cer-Mg) in the treatment of mild to moderate atopic dermatitis and to compare it with hydrocortisone and a commonly used emollient (unguentum leniens; cold cream). A total of 100 patients, randomized into 2 groups, were treated for 6 weeks simultaneously (left vs. right side of the body) with either Cer-Mg and hydrocortisone (group I) or Cer-Mg and emollient (group II). The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 35 publications
1
43
0
4
Order By: Relevance
“…Local application of the ointment over 6 days diminished this uptake and prevented increased transepidermal penetration of this allergen. These findings are in line with studies that show clear beneficial effects of ceramide‐containing ointments in improving the clinical symptoms and skin barrier of patients with AD …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Local application of the ointment over 6 days diminished this uptake and prevented increased transepidermal penetration of this allergen. These findings are in line with studies that show clear beneficial effects of ceramide‐containing ointments in improving the clinical symptoms and skin barrier of patients with AD …”
Section: Discussionsupporting
confidence: 91%
“…The alteration in skin barrier plays a major role in the pathophysiology of this disease as it leads to increased penetration by environmental allergens and infective organisms that cause persistent inflammation . The main contributor to the skin barrier is the stratum corneum, which is based on the “brick and mortar” structure that is composed of corneocytes surrounded by lipid lamellae comprised of ceramides, cholesterol, and free fatty acids . AD lesions exhibit reduced levels of ceramides in the stratum corneum and changes in their relative composition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mg salts are known to enhance skin hydration, dermal permeability, and barrier repair and to facilitate epidermal proliferation and differentiation, thus reducing inflammation [123, 124]. A double-blind controlled trial using a cream containing Mg along with ceramides (a family of waxy lipid molecules found in high concentrations within the cell membrane) to treat mild-to-moderate atopic dermatitis was found to be superior to hydrocortisone creams [125]. Accordingly, there may be beneficial uses of Mg for assorted skin conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In a double‐blind randomized clinical trial of patients with mild AD, it was shown (split‐side comparison) that application of a topical agent containing ceramides resulted in a significantly greater improvement in the SCORAD index than basic skin care with cold cream. The reduction in the SCORAD index was equivalent to that produced by topical treatment with hydrocortisone alone (split‐side comparison) .…”
Section: Basic Skin Care (Basic Therapy)mentioning
confidence: 97%